Psychometric Properties of the German Version of the Self-Regulation of Eating Behavior Questionnaire - Schmalbach, Ileana; Schmalbach, Bjarne; Zenger, Markus; Petrowski, Katja; Beutel, Manfred; Hilbert, Anja; Brähler, Elmar (Frontiers in Psychology, 2021)
Background: The Self-Regulation of Eating Behavior Questionnaire (SREBQ) is an economical way of assessing an individual’s self-regulatory abilities regarding eating behavior. Such scales are also needed in the German population, therefore, the purpose of the present study was the translation and validation of a German version of the SREBQ. Method: First, we conducted a pilot study (Study 1) after the translation procedure. Second, we assessed the final scale in a population-based sample (Sample 2) and its underlying factor structure. Further, we tested for measurement invariance and evaluated the SREBQ’s associations with related scales to explore convergent and discriminant validity. Finally, we considered differences in SREBQ based on sociodemographic variables and provided norm values. Results: Factor analysis revealed deficiencies in the original model. Thus, we shortened the scale based on statistical considerations and the adapted version showed improved fit in Confirmatory Factor Analysis and reliability. We also found evidence for partial strict invariance, which means the measure is equivalent for the tested groups of age and gender. Item and scale characteristics of the shortened version were satisfactory. In terms of diagnostic validity, it was shown that individuals with higher Body Mass Index (Kg/m2) have worse self-regulation of eating behavior than those with lower. Conclusion: In sum, the SREBQ evidenced good validity and reliability and it is suitable for application in medical, psychological, and nutritional research.